2015
DOI: 10.2967/jnumed.115.161802
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 6-11C-Methyl-m-Tyrosine as a PET Probe for Presynaptic Dopaminergic Activity: A Comparison PET Study with β-11C-l-DOPA and 18F-FDOPA in Parkinson Disease Monkeys

Abstract: We recently developed a novel PET probe, 6-11 C-methyl-m-tyrosine ( 11 C-6MemTyr), for quantitative imaging of presynaptic dopamine synthesis in the living brain. In the present study, 11 C-6MemTyr was compared with β-11 C-L-DOPA and 6-18 F-fluoro-L-dopa ( 18 F-FDOPA) in the brains of normal and Parkinson disease (PD) model monkeys (Macaca fascicularis). Methods: PD model monkeys were prepared by 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) administration, and 11 C-β-CFT was applied to assess neuronal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…We previously confirmed that the degeneration of nigrostriatal dopamine neurons was induced by the intravenous administration of MPTP to monkeys over a period of several months and resulted in impaired presynaptic dopamine parameters, as determined by DAT availability, dopamine synthesis, and tyrosine hydroxylase immunoreactivity in the brain (9,10). A previous study reported that although plotting the striatal MTGA Ki values of 11 C-6MemTyr, b-11 C-L-DOPA, and 18 F-FDOPA against the BP ND of 11 C-b-CFT in the striatum of monkeys revealed positive correlations, the Ki value of 11 C-6MemTyr provided greater correlation coefficients than b-11 C-L-DOPA and 18 F-FDOPA (10). The present study also demonstrated that the most sensitive PET probe for the detection of impaired MC-I activity was 11 C-6Mem-Tyr.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…We previously confirmed that the degeneration of nigrostriatal dopamine neurons was induced by the intravenous administration of MPTP to monkeys over a period of several months and resulted in impaired presynaptic dopamine parameters, as determined by DAT availability, dopamine synthesis, and tyrosine hydroxylase immunoreactivity in the brain (9,10). A previous study reported that although plotting the striatal MTGA Ki values of 11 C-6MemTyr, b-11 C-L-DOPA, and 18 F-FDOPA against the BP ND of 11 C-b-CFT in the striatum of monkeys revealed positive correlations, the Ki value of 11 C-6MemTyr provided greater correlation coefficients than b-11 C-L-DOPA and 18 F-FDOPA (10). The present study also demonstrated that the most sensitive PET probe for the detection of impaired MC-I activity was 11 C-6Mem-Tyr.…”
Section: Discussionmentioning
confidence: 94%
“…The present study also demonstrated that the most sensitive PET probe for the detection of impaired MC-I activity was 11 C-6Mem-Tyr. The different abilities of b-11 C-L-DOPA, 18 F-FDOPA, and 11 C6MemTyr to detect presynaptic dopamine damage may be attributed to their different metabolic profiles on the basis of catechol-(b-11 C-L-DOPA and 18 F-FDOPA) and noncatechol-type ( 11 C-6MemTyr) structures (10).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations